Land Management On Individually Held Lands Under The Indian Act Reserve Land Tenure System: Experiences from the Penticton Indian Band - Brinkhurst, Marena; Phillip, Joan; Rutherford, Murray B. (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2013)
This paper is based on case study research with the Penticton Indian Band (PIB) that examined the land management implications of individual landholdings (Certificates of Possession, CPs) on First Nations reserves under the Indian Act, both historically and today. We summarize the history of the landholdings system on PIB's main reserve and report on how CPs impact PIB's contemporary local land management. We also discuss PIB's efforts to adapt its land tenure and management systems locally while continuing to operate within the overall land management framework of the Indian Act; efforts that make PIB's experiences particularly interesting for other First Nations and their land managers, federal officials and policy makers, and researchers. Our objective in this paper is to complement and broaden existing research on CPs by focusing on land management challenges from PIB's experiences.